PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN BUDAYA SEKOLAH TERHADAP KOMPETENSI GURU SD NEGERI DI KECAMATAN SEBAWI - Ambri, Amat; Amin, Maswardi Muhammad; Wahyudi, Wahyudi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This research generally aimd to reveal the relationship of learning leadership and emotional intelligence principals and achievement motivation Junior High School teacher in Subrayon XI Sebawi Sambas District. This study used a quantitative approach. The data used was quantitative data. Population as well as a sample in this study amounted to 77 teachers. Data were collected using a questionnaire with measurement models using Likert scale. The collected data was tabulated. Then analyzed with the help of a computer application program, SPSS version 16 for Window. Data analysis using descriptive statistics and inferential statistics. The initial step in testing the hypothesis, that the test requirements regression analysis (test for normality and linearity test). After the test analysis requirements are met, then that hypothesis testing. The analysis technique used was multiple regression analysis. To determine the influence of independent variables on the dependent variable was jointly used by test F. The results showed that 1) the relationship of learning leadership principals (X1) and achievement motivation of teachers (Y) Beta (b1) of 0,334 = 33.40%, 2) the relationship of emotional intelligence principals (X2) and achievement motivation of teachers (Y) beta (b1) of 0.442 = 44.20%, 3) relationships principals instructional leadership (X1) and emotional intelligence principals (X2) and achievement motivation of teachers of 0.446 or 44.60%. The test results were shown in the output F ANOVA results of multiple linear regression analysis showed that F count> F table (45.4959> 3.115).The conclusion of this study as follows: 1) leadership learning Junior high school principal State in Subrayon XI Sebawi Sambas District quite good, 2) emotional intelligence principals SMP in Sub Rayon XI Sebawi Sambas District is high, 3) achievement motivation of teachers SMP in Sub Rayon XI Sebawi Sambas District classified satisfactory, 4) leadership learning school principals relate very significant achievement motivation of teachers SMP in Sub Rayon XI Sebawi Sambas District, of 0,334 = 33.40%, Keywords: Learning Leadership, Emotional Intelligence, Principal, Teacher Achievement Motivation